Influence of pretreatment ideal body weight percentile and albumin on prognosis of nasopharyngeal carcinoma: Long‐term outcomes of 512 patients from a single institution. Issue 5 (30th July 2013) - Li, Guo; Gao, Jin; Liu, Zhi‐Gang; Tao, Ya‐Lan; Xu, Bing‐Qing; Tu, Zi‐Wei; Zhang, Xiu‐Ping; Zeng, Mu‐Sheng; Xia, Yun‐Fei
ABSTRACT Background The purpose of this study was to investigate the relationship between pretreatment nutritional status and prognosis of nasopharyngeal carcinoma (NPC). Methods Pretreatment nutritional status was evaluated by ideal body weight percentile (IBW%) and serum albumin for 512 patients with NPC who underwent radical radiotherapy. Kaplan–Meier methods, log‐rank test, and a Cox model were applied for survival analysis. Results Before radiotherapy, IBW% <90% was related to poorer overall survival (OS) and distant metastasis–free survival (DMFS; p = .031 and p = .012, respectively); albumin ≤43.0 g/L was related to poorer OS and DMFS (p < .001 and p = .042, respectively); both IBW% and albumin were independent prognostic factors for OS; those patients with IBW% <90% and albumin ≤43.0 g/L simultaneously had the worst OS and DMFS. Conclusion Decrease of pretreatment IBW% and albumin was related to poorer survival of NPC. © 2013 Wiley Periodicals, Inc. Head Neck36: 660–666, 2014